Clinicopathological correlates of adrenal Cushing's syndrome. Issue 3 (25th November 2014) - Duan, Kai; Hernandez, Karen Gomez; Mete, Ozgur
Abstract : Endogenous Cushing's syndrome is a rare endocrine disorder that incurs significant cardiovascular morbidity and mortality, due to glucocorticoid excess. It comprises adrenal (20%) and non-adrenal (80%) aetiologies. While the majority of cases are attributed to pituitary or ectopic corticotropin (ACTH) overproduction, primary cortisol-producing adrenal cortical lesions are increasingly recognised in the pathophysiology of Cushing's syndrome. Our understanding of this disease has progressed substantially over the past decade. Recently, important mechanisms underlying the pathogenesis of adrenal hypercortisolism have been elucidated with the discovery of mutations in cyclic AMP signalling ( PRKACA, PRKAR1A, GNAS, PDE11A, PDE8B ), armadillo repeat containing 5 gene ( ARMC5 ) a putative tumour suppressor gene, aberrant G-protein-coupled receptors, and intra-adrenal secretion of ACTH. Accurate subtyping of Cushing's syndrome is crucial for treatment decision-making and requires a complete integration of clinical, biochemical, imaging and pathology findings. Pathological correlates in the adrenal glands include hyperplasia, adenoma and carcinoma. While the most common presentation is diffuse adrenocortical hyperplasia secondary to excess ACTH production, this entity is usually treated with pituitary or ectopic tumour resection. Therefore, when confronted with adrenalectomy specimens in the setting of Cushing's syndrome, surgical pathologists are most commonly exposed to adrenocortical adenomas, carcinomas and primary macronodular or micronodular hyperplasia. This review provides an update on the rapidly evolving knowledge of adrenal Cushing's syndrome and discusses the clinicopathological correlations of this important disease.